Thermosetting resin composition, cured product, and printed wiring board

A thermosetting resin composition with hydroxyl-containing fluororesin, isocyanate compound, and rutile titanium oxide addresses the balance of flexibility, reflectivity, and heat resistance in printed wiring boards, enhancing performance for LEDs.

CN116323743BActive Publication Date: 2024-12-31TAIYO HOLDINGS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202180069605.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2020-11-17
Filing Date
2021-11-16
Publication Date
2024-12-31
Estimated Expiration
2041-11-16

AI Technical Summary

Technical Problem

Existing printed wiring boards with solder resist layers face challenges in achieving a balance between flexibility, reflectivity, and heat resistance, particularly in thin film substrates, leading to issues like poor reflectivity, heat resistance, and warping.

Method used

A thermosetting resin composition containing a hydroxyl-containing fluororesin, an isocyanate compound with two or more isocyanate groups, and rutile titanium oxide, with specific mass ratios, is used to form a resin layer that achieves an excellent balance of flexibility, reflectivity, and heat resistance.

Benefits of technology

The resin composition forms a cured product with improved reflectivity, heat resistance, and reduced warping, suitable for flexible and rigid substrates, including those used in surface-mounted LEDs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure GDA0004171374770000121
    Figure GDA0004171374770000121
  • Figure GDA0004171374770000131
    Figure GDA0004171374770000131
  • Figure GDA0004171374770000141
    Figure GDA0004171374770000141
Patent Text Reader

Abstract

The problem is to provide a thermosetting resin composition that can form a resin layer with an excellent balance of flexibility, reflectivity, heat resistance and warpage. The thermosetting resin composition of the solution is characterized by containing a hydroxyl-containing fluororesin, an isocyanate compound having two or more isocyanate groups, and rutile titanium oxide, wherein the mass ratio of the fluororesin to the isocyanate compound is 1 or more and 20 or less, and the mass ratio of the rutile titanium oxide to the fluororesin is 1.4 or more and 4 or less. In addition, the thermosetting resin composition of the present invention contains a hydroxyl-containing fluororesin, an isocyanate compound having two or more isocyanate groups, and rutile titanium oxide, wherein, when the elemental analysis is performed on the cured product obtained by curing the thermosetting resin composition by a combustion method, when the whole is defined as 100 mass%, it is detected that the ash content is 45 mass% or more, the fluorine atoms are 3 mass% or more, and the nitrogen atoms are 0.1 mass% or more.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a thermosetting resin composition. The present invention also relates to a cured product obtained by curing the thermosetting resin composition. The present invention also relates to a printed wiring board having a resin layer composed of the cured product. Background Art

[0002] In recent years, due to the demand for energy-saving electrical products, light-emitting diodes (LEDs) as low-power, long-life light sources have rapidly become popular. LEDs are used as backlights of liquid crystal displays such as mobile terminals, personal computers, and televisions, or as light sources for lighting equipment. At this time, LEDs that are directly mounted on printed wiring boards covered with a resist layer, so-called surface-mounted LEDs, are increasingly being used.

[0003] In surface mounted LEDs, in order to efficiently utilize the light of the LED, a printed wiring board having a resist layer with high reflectivity is required. In order to meet this requirement, it has been proposed to obtain bright white lighting by adding a white colorant to a resin composition forming the resist layer.

[0004] For example, Patent Document 1 discloses that, in the manufacture of a wiring board for mounting a light-emitting element, by configuring a non-fluorine-based white solder resist as a lower layer and a fluorine-based white solder resist as an upper layer on an insulating substrate as an anti-etching layer, the heat resistance of the solder can be ensured, thereby saving the labor of attaching a reflective sheet and being able to meet the high reflectivity requirements for a long time.

[0005] Prior art literature

[0006] Patent Literature

[0007] Patent document 1: Japanese Patent Application Publication No. 2016-63132. Summary of the invention

[0008] Problems to be solved by the invention

[0009] The present inventors have found that the structure of the wiring board for mounting a light emitting element described in Patent Document 1 requires a non-fluorine-based solder resist layer to be formed on an insulating substrate, and that this has a problem of poor reflectivity and heat resistance compared to the case of forming only a fluorine-based solder resist layer.

[0010] In addition, in recent years, in order to be used in flexible printed wiring boards, the solder resist layer is also required to be flexible. In addition, even for rigid substrates, thin film substrates are used to meet the requirements for thin film backlights. In the structure described in Patent Document 1, it is known that the problem of warping in thin film substrates is relatively large. It is also known that there are problems with heat resistance. That is, in the white solder resists so far, there is a problem that a structure with excellent balance between reflectivity, heat resistance and warping cannot be achieved.

[0011] Therefore, an object of the present invention is to provide a thermosetting resin composition capable of forming a resin layer having an excellent balance among flexibility, reflectivity, heat resistance and warpage. In addition, an object of the present invention is to provide a cured product obtained by curing the thermosetting resin composition and a printed wiring board having the cured product.

[0012] Means for solving problems

[0013] As a result of intensive studies, the present inventors have discovered that the above-mentioned problems can be solved by adding a hydroxyl-containing fluororesin, an isocyanate compound having two or more isocyanate groups, and rutile titanium oxide to a thermosetting resin composition, and adjusting the mass ratio of the fluororesin to the isocyanate compound and the mass ratio of the rutile titanium oxide to the fluororesin, thereby completing the present invention.

[0014] Furthermore, as a result of intensive studies, the present inventors have discovered that the above-mentioned problems can be solved by adding a hydroxyl-containing fluororesin, an isocyanate compound having two or more isocyanate groups, and rutile titanium oxide to a thermosetting resin composition, performing elemental analysis on the cured product obtained by curing the thermosetting resin composition by a combustion method, and adjusting the ratio of ash content, fluorine atoms, and nitrogen atoms, thereby completing the present invention.

[0015] That is, the thermosetting resin composition of the present invention is characterized in that it contains: a hydroxyl-containing fluororesin; an isocyanate compound having two or more isocyanate groups; and rutile titanium oxide, wherein the mass ratio of the fluororesin to the isocyanate compound is greater than 1 and less than 20, and the mass ratio of the rutile titanium oxide to the fluororesin is greater than 1.4 and less than 4.

[0016] In addition, the thermosetting resin composition of the present invention containing a hydroxyl-containing fluororesin, an isocyanate compound having two or more isocyanate groups, and rutile titanium oxide is characterized in that, when an elemental analysis is performed on a cured product obtained by curing the thermosetting resin composition by a combustion method, when the whole is defined as 100 mass%, an ash content of 45 mass% or more, a fluorine atom of 3 mass% or more, and a nitrogen atom of 0.1 mass% or more are detected.

[0017] In the aspect of the present invention, it is preferred that the mass ratio of the fluororesin to the isocyanate compound is 2 to 10, and the mass ratio of the rutile titanium oxide to the fluororesin is 1.8 to 3.5.

[0018] In the embodiment of the present invention, the fluororesin is preferably a hydrolyzate of a copolymer of a fluorine-containing vinyl monomer and a vinyl ester monomer or a copolymer of a fluorine-containing vinyl monomer and a hydroxyl-containing vinyl monomer.

[0019] In the scheme of the present invention, it is preferred that the fluorine-containing vinyl monomer is tetrafluoroethylene.

[0020] In the embodiment of the present invention, the isocyanate compound is preferably a blocked isocyanate.

[0021] In the aspect of the present invention, it is preferred that the isocyanate compound contains a group containing an alkyl group, or a group containing an ether group and / or a silicate group.

[0022] In the aspect of the present invention, it is preferred that a storage modulus of a cured product obtained by curing the thermosetting resin composition is 0.02 GPa or more and 20 GPa or less at 20°C.

[0023] In the aspect of the present invention, it is preferred that the thermosetting resin composition is used for a resin layer formed directly on an insulating substrate.

[0024] A cured product according to another aspect of the present invention is obtained by curing the curable resin composition.

[0025] A printed wiring board according to another aspect of the present invention is characterized by comprising a resin layer composed of the above-mentioned cured product.

[0026] A printed wiring board according to another aspect of the present invention is preferably used for a surface-mounted LED.

[0027] Effects of the Invention

[0028] According to the present invention, a thermosetting resin composition capable of forming a resin layer having an excellent balance among flexibility, reflectivity, heat resistance and warpage can be provided. In addition, according to the present invention, a cured product obtained by curing the thermosetting resin composition and a printed wiring board having a resin layer composed of the cured product can be provided. DETAILED DESCRIPTION

[0029] [Thermosetting resin composition]

[0030] The thermosetting resin composition of the present invention contains a hydroxyl-containing fluororesin, an isocyanate compound having two or more isocyanate groups, and rutile titanium oxide. Since the thermosetting resin composition of the present invention can form a cured product having an excellent balance of flexibility, reflectivity, heat resistance, and warpage, it is suitable for use in a resin layer directly formed on an insulating substrate of a printed wiring board. In particular, in order to improve the reflectivity of the cured product (resin layer), the resin layer is preferably white.

[0031] The cured product obtained by curing the thermosetting resin composition is subjected to elemental analysis by the combustion method. When the whole is defined as 100% by mass, the ash content is detected to be 45% by mass or more, preferably 50% by mass or more and 90% by mass or less, more preferably 60% by mass or more and 80% by mass or less, the fluorine atoms are 3% by mass or more, preferably 4% by mass or more and 20% by mass or less, more preferably 5% by mass or more and 15% by mass or less, and the nitrogen atoms are 0.1% by mass or more, preferably 0.2% by mass or more and 5% by mass or less, more preferably 0.3% by mass or more and 3% by mass or less. It should be noted that the elemental analysis by the combustion method can be carried out by the method described in the embodiments described later. When the result of the elemental analysis is in the case of the above-mentioned numerical value, it becomes evidence of the amount of fluorine resin, the amount of isocyanate compound, and the amount of titanium oxide that can ensure the formation of a resin layer with excellent balance of flexibility, reflectivity, heat resistance and warping.

[0032] The elastic modulus of the cured product obtained by curing the thermosetting resin composition is preferably 0.02 GPa or more and 20 GPa or less at 20°C, and more preferably 0.2 GPa or more and 10 GPa or less at 20°C. It should be noted that the elastic modulus is a value of a cured product having a film thickness of 200 μm or more and 600 μm or less measured using a dynamic viscoelasticity measuring device (DMA). When the elastic modulus is within the above numerical range, warping does not occur even when applied to a substrate, and the hardness can also be used as a resist film.

[0033] Hereinafter, each component constituting the thermosetting resin composition of the present invention will be described.

[0034] [Fluororesin]

[0035] The fluororesin can be used without particular limitation as long as it has a hydroxyl group. The fluororesin preferably does not have a chlorine group from the viewpoint of reducing the reflectivity of the cured product of the thermosetting resin composition or increasing impurities.

[0036] As the hydroxyl-containing fluororesin, copolymers of fluorine-containing vinyl monomers and hydroxyl-containing vinyl monomers, and hydrolyzates of copolymers of fluorine-containing vinyl monomers and vinyl ester monomers can be used appropriately. The hydroxyl-containing fluororesin can be used alone or in combination of two or more.

[0037] As fluorine-containing vinyl monomers, tetrafluoroethylene, hexafluoropropylene, trifluoroethylene, etc. can be cited. From the viewpoint of reduced reflectivity or increased impurities in the cured product of the thermosetting resin composition, the fluorine-containing monomer preferably does not have a chlorine group, and tetrafluoroethylene is particularly preferred. These fluorine-containing monomers can be used alone or in combination of two or more.

[0038] As hydroxyl-containing vinyl monomers, for example, 2-hydroxyethyl vinyl ether, 3-hydroxypropyl vinyl ether, 2-hydroxypropyl vinyl ether, 2-hydroxy-2-methylpropyl vinyl ether, 4-hydroxybutyl vinyl ether, 4-hydroxy-2-methylbutyl vinyl ether, 5-hydroxypentyl vinyl ether, 6-hydroxyhexyl vinyl ether and other hydroxyl-containing vinyl ethers; 2-hydroxyethyl allyl ether, 4-hydroxybutyl allyl ether, glycerol monoallyl ether and other hydroxyl-containing allyl ethers, vinyl alcohol and the like can be cited. These hydroxyl-containing monomers can be used alone or in combination of two or more. In addition, as vinyl ester monomers, for example, vinyl acetate, vinyl propionate, vinyl formate and the like can be cited.

[0039] The amount of the fluororesin blended is preferably 10% by mass or more and 50% by mass or less, more preferably 15% by mass or more and 45% by mass or less, and further preferably 18% by mass or more and 35% by mass or less, calculated as a solid content per part of the thermosetting resin composition. By making the amount of the fluororesin blended within the above range, a cured product having excellent heat resistance can be obtained.

[0040] [Isocyanate compound]

[0041] The isocyanate compound can be used without particular limitation as long as it has two or more isocyanate groups. The isocyanate compound reacts with the above-mentioned fluororesin to form a urethane bond to form a cured product. In particular, the isocyanate compound preferably contains a group containing a chain alkyl group, or a group containing an ether group and / or a silicate group.

[0042] As the isocyanate compound, a polyisocyanate compound can be combined. As the polyisocyanate compound, aromatic polyisocyanates such as 4,4'-diphenylmethane diisocyanate, 2,4-toluene diisocyanate, 2,6-toluene diisocyanate, naphthalene-1,5-diisocyanate, o-xylyl diisocyanate, m-xylyl diisocyanate and 2,4-toluene dimer can be cited; aliphatic polyisocyanates such as tetramethylene diisocyanate, hexamethylene diisocyanate, methylene diisocyanate, trimethylhexamethylene diisocyanate, 4,4-methylenebis(cyclohexyl isocyanate) and isophorone diisocyanate; alicyclic polyisocyanates such as dicycloheptane triisocyanate; and adducts, biuret bodies and isocyanurate bodies of the isocyanate compounds listed above. The isocyanate compound can be used alone or in combination of two or more.

[0043] In the present invention, the isocyanate compound is preferably a blocked isocyanate compound from the viewpoint of excellent storage stability and improved handleability.

[0044] As the blocked isocyanate compound, an addition reaction product of an isocyanate compound and an isocyanate blocking agent can be used. As the isocyanate compound that can react with the isocyanate blocking agent, for example, the above-mentioned polyisocyanate compounds and the like can be cited. As the isocyanate blocking agent, for example, phenol-based blocking agents such as phenol, cresol, xylenol, chlorophenol and ethylphenol; lactam-based blocking agents such as ε-caprolactam, δ-valerolactam, γ-butyrolactam and β-propiolactam; alcohol-based blocking agents such as methanol, ethanol, propanol, butanol, pentanol, ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, ethylene glycol monobutyl ether, diethylene glycol monomethyl ether, propylene glycol monomethyl ether, benzyl ether, methyl glycolate, butyl glycolate, diacetone alcohol, methyl lactate and ethyl lactate; formaldehyde oxime, acetaldehyde oxime, acetone oxime, methyl ethyl ketone Oxime-based capping agents such as oxime, diacetyl monoxime, and cyclohexanone oxime; thiol-based capping agents such as butyl mercaptan, hexyl mercaptan, tert-butyl mercaptan, thiophenol, methylthiophenol, and ethylthiophenol; acid amide-based capping agents such as acetamide and benzamide; imide-based capping agents such as succinimide and maleic imide; amine-based capping agents such as dimethylaniline, aniline, butylamine, and dibutylamine; imidazole-based capping agents such as imidazole and 2-ethylimidazole; imine-based capping agents such as methyleneimine and propyleneimine; pyrazole-based capping agents such as dimethylpyrazole; maleate-based capping agents such as diethylmaleic acid, etc.

[0045] Examples of commercially available blocked isocyanate compounds include Desmodur (registered trademark) BL-3175, BL-4265, BL-1100 / 1, BL-1265 / 1, TPLS-2957, TPLS-2062, TPLS-2078, TPLS-2117, Desmotherm 2170, and Desmotherm 2265 (all manufactured by Sumitomo Bayer Polyurethanes Co., Ltd.), Coronate (registered trademark) 2512, Coronate 2513, and Coronate 2520 (all manufactured by Tosoh Corporation), B-830, B-815, B-846, B-870, B-874, and B-882 (all manufactured by Mitsui Chemicals Polyurethanes Co., Ltd.), and Duranate. SBN-70D, TPA-B80E, 17B-60P, E402-B80B (all manufactured by Asahi Kasei Corporation), TRIXENE BI 7982, TRIXENE BI 7950, TRIXENE BI 7951, TRIXENE BI 7960, TRIXENE BI 7961 (manufactured by Baxeneden Chemicals Limited), among which Duranate SBN-70D and TRIXENE BI 7982 are preferred. Desmodur BL-3175 and BL-4265 are obtained by using methylethyl oxime as a terminal blocking agent.

[0046] The mass ratio of the fluororesin to the isocyanate compound is 1 to 20, preferably 2 to 10, in terms of solid content. When the mass ratio of the fluororesin to the isocyanate compound is within the above numerical range, a cured product having excellent heat resistance can be obtained by the curing reaction with the fluororesin.

[0047] The amount of the isocyanate compound is preferably 0.1% by mass or more and 30% by mass or less, more preferably 1% by mass or more and 20% by mass or less, and further preferably 1% by mass or more and 15% by mass or less, calculated as the solid content per part of the thermosetting resin composition. By making the amount of the isocyanate compound within the above range, a cured product having excellent heat resistance can be obtained.

[0048] [Titanium oxide]

[0049] As titanium oxide, rutile titanium oxide and anatase titanium oxide can be cited, but rutile titanium is used in the present invention. As the same titanium oxide, anatase titanium oxide has a higher whiteness than rutile titanium oxide and is generally used as a white colorant. However, since anatase titanium oxide has photocatalytic activity, there is a risk of discoloration of the resin in the resin layer due to light irradiated from an LED in particular. On the other hand, since rutile titanium oxide has a slightly worse whiteness than anatase titanium oxide but has almost no photoactivity, the degradation (yellowing) of the resin caused by light due to the photoactivity of titanium oxide is significantly suppressed, and it is also stable to heat. Therefore, when used as a white colorant in the resin layer of a printed wiring board on which an LED is installed, high reflectivity can be maintained for a long time.

[0050] As rutile titanium oxide, known rutile titanium oxide can be used. There are two methods for manufacturing rutile titanium oxide, namely, a sulfuric acid method and a chlorine method. In the present invention, rutile titanium oxide manufactured by any of the manufacturing methods can be appropriately used. Here, the sulfuric acid method refers to a method for manufacturing ilmenite ore or titanium slag as a raw material, dissolving it in concentrated sulfuric acid, separating the iron component as ferric sulfate, obtaining a hydroxide precipitate by hydrolyzing the solution, and calcining it at a high temperature to extract rutile titanium oxide. On the other hand, the chlorine method refers to a method for manufacturing synthetic rutile or natural rutile as a raw material, reacting it with chlorine and carbon under a high temperature condition of about 1000°C to synthesize titanium tetrachloride, and oxidizing it to extract rutile titanium oxide. Among them, the rutile titanium oxide manufactured by the chlorine method has a particularly significant inhibitory effect on the deterioration (yellowing) of the resin caused by heat, and is more suitable for the present invention.

[0051] As the rutile titanium oxide, titanium oxide whose surface is treated with hydrous aluminum oxide, aluminum hydroxide and / or silicon dioxide can be used. By using the surface-treated rutile titanium oxide, the dispersibility in the thermosetting resin composition, the storage stability, the flame retardancy, etc. can be improved.

[0052] The average particle size of rutile titanium oxide is preferably 0.1 μm or more and 1.0 μm or less, more preferably 0.2 μm or more and 0.8 μm or less. In particular, as rutile titanium oxide, rutile titanium oxide preferably has a particle size of 0.25 μm, which accounts for more than 1% of the total particles. In this specification, the average particle size of rutile titanium oxide is an average particle size (D50) that includes not only the particle size of primary particles but also the particle size of secondary particles (agglomerates), and the value of D50 measured by laser diffraction method. As a measuring device for the laser diffraction method, Microtrac MT3300EXII manufactured by Microtrac Bell can be cited.

[0053] As the rutile titanium oxide, a commercially available item can also be used. Examples of commercially available rutile titanium oxide include TIPAQUE R-820, TIPAQUE R-830, TIPAQUE R-930, TIPAQUE R-550, TIPAQUE R-630, TIPAQUE R-680, TIPAQUE R-670, TIPAQUE R-780, TIPAQUE R-850, TIPAQUE CR-50, TIPAQUE CR-57, TIPAQUE CR-80, TIPAQUE CR-90, TIPAQUE 90-2, TIPAQUE CR-93, TIPAQUE CR-95, TIPAQUE CR-97, TIPAQUE CR-63, TIPAQUE CR-58, and TIPAQUE UT771 (manufactured by Ishihara Sangyo Co., Ltd.), TI-PURE R-101, TI-PURE R-103, TI-PURE R-104, and TI-PURE R-105, TI-PURE R-108, TI-PURE R-900, TI-PURE R-902+, TI-PURE R-960, TI-PURE R-706 (manufactured by DuPont), TITONE R-25, R-21, R-32, R-7E, R-5N, R-62N, R-42, R-45M, GTR-100, D-918 (manufactured by Sakai Chemical Industry Co., Ltd.), etc.

[0054] The mass ratio of rutile titanium oxide to fluororesin is 1.4 to 4, preferably 1.8 to 3.5, more preferably more than 2 to 3.5, in terms of solid content. When the mass ratio of rutile titanium oxide to fluororesin is within the above numerical range, the resin layer can obtain high reflectivity.

[0055] The amount of rutile titanium oxide is preferably 50% by mass or more, more preferably 55% by mass or more and 80% by mass or less, and further preferably 60% by mass or more and 75% by mass or less, based on the solid content per part of the thermosetting resin composition. When the amount of rutile titanium oxide is 50% by mass or more, the resin layer can obtain a high reflectivity.

[0056] The thermosetting resin composition of the present invention may further contain the following optional components.

[0057] [Silicon dioxide]

[0058] The silica may be any known silica that can be used as a filler for electronic materials. The silica may be used alone or in combination of two or more.

[0059] As silica, there can be mentioned fused silica, spherical silica, amorphous silica, crystalline silica, fine powder silica, etc. Among them, spherical silica is preferred from the viewpoint of the fluidity of the thermosetting resin composition. The shape of the spherical silica is spherical, and is not limited to a true sphere.

[0060] The average particle size of silicon dioxide is 0.01 μm or more and 10 μm or less, and preferably 0.05 μm or more and 5 μm or less. In the present specification, the average particle size of silicon dioxide can be measured in the same manner as the average particle size of titanium oxide described above.

[0061] As the silica, either unsurface-treated silica or surface-treated silica can be used.

[0062] The amount of silicon dioxide is preferably 1% by mass or more and 20% by mass or less, more preferably 2% by mass or more and 15% by mass or less, and further preferably 3% by mass or more and 10% by mass or less, calculated according to the solid content of each thermosetting resin composition. By making the amount of silicon dioxide in the above range, the reflectivity of the resin layer can be improved. Silicon dioxide is not particularly necessary, but it is preferably matched in terms of advantageous effects such as the effect of improving the reflectivity that can be observed.

[0063] [Thermal Curing Catalyst]

[0064] The thermosetting resin composition of the present invention may be formulated with a thermosetting catalyst. Examples of the thermosetting catalyst include imidazole derivatives such as imidazole, 2-methylimidazole, 2-ethylimidazole, 2-ethyl-4-methylimidazole, 2-phenylimidazole, 4-phenylimidazole, 1-cyanoethyl-2-phenylimidazole, and 1-(2-cyanoethyl)-2-ethyl-4-methylimidazole; amine compounds such as dicyandiamide, benzyldimethylamine, 4-(dimethylamino)-N,N-dimethylbenzylamine, 4-methoxy-N,N-dimethylbenzylamine, and 4-methyl-N,N-dimethylbenzylamine; hydrazine compounds such as adipic acid dihydrazide and sebacic acid dihydrazide; and phosphorus compounds such as triphenylphosphine. In addition, commercially available products include, for example, 2MZ-A, 2MZ-OK, 2PHZ, 2P4BHZ, and 2P4MHZ (all trade names of imidazole compounds) manufactured by Shikoku Chemical Industry Co., Ltd., U-CAT 3513N (a trade name of a dimethylamine compound) manufactured by San-Apro Co., Ltd., DBU, DBN, and U-CAT SA 102 (all bicyclic amidine compounds and salts thereof), etc. In addition, guanamine, acetoguanamine, benzoguanamine, melamine, 2,4-diamino-6-methacryloyloxyethyl-S-triazine, 2-vinyl-2,4-diamino-S-triazine, 2-vinyl-4,6-diamino-S-triazine-isocyanuric acid adduct, 2,4-diamino-6-methacryloyloxyethyl-S-triazine-isocyanuric acid adduct and other S-triazine derivatives can be used, and these compounds that also function as adhesion-imparting agents are preferably used in combination with a thermal curing catalyst. The thermal curing catalyst may be used alone or in combination of two or more.

[0065] The amount of the thermosetting catalyst to be added is preferably 0.1 to 5 parts by mass, more preferably 1 to 3 parts by mass, based on the solid content of the total amount of the thermosetting resin composition.

[0066] [Organic solvents]

[0067] The thermosetting resin composition of the present invention may contain an organic solvent for the purpose of preparing the composition, adjusting the viscosity when coating on a substrate or a film, etc. As the organic solvent, ketones such as methyl ethyl ketone and cyclohexanone; aromatic hydrocarbons such as toluene, xylene, and tetramethylbenzene; glycol ethers such as cellosolve, methyl cellosolve, butyl cellosolve, carbitol, methyl carbitol, butyl carbitol, propylene glycol monomethyl ether, dipropylene glycol monomethyl ether, dipropylene glycol diethyl ether, diethylene glycol monomethyl ether acetate, and tripropylene glycol monomethyl ether; esters such as ethyl acetate, butyl acetate, butyl lactate, cellosolve acetate, butyl cellosolve acetate, diethylene glycol monoethyl ether acetate, butyl carbitol acetate, propylene glycol monomethyl ether acetate, dipropylene glycol monomethyl ether acetate, and propylene carbonate; aliphatic hydrocarbons such as octane and decane; petroleum-based solvents such as petroleum ether, petroleum naphtha, and solvent naphtha, etc., and well-known and commonly used organic solvents can be used. Among them, when a porous substance such as amorphous silica is used in the thermosetting resin composition of the present invention, esters are preferred, and diethylene glycol monoethyl ether acetate is more preferred, because the silica surface easily absorbs oil during curing or drying, resulting in a lower glossiness of the formed cured coating film. These organic solvents may be used alone or in combination of two or more.

[0068] The amount of the organic solvent added is not particularly limited and can be appropriately set according to the target viscosity so that the thermosetting resin composition can be easily prepared.

[0069] [Other added ingredients]

[0070] In the thermosetting resin composition of the present invention, it is possible to further coordinate, as required, thixotropic agent, close-fitting promoter, block copolymer, chain transfer agent, polymerization inhibitor, copper poison inhibitor, antioxidant, rust inhibitor, micro powder silica, organic bentonite, thickener such as montmorillonite, at least one of defoamers and leveling agents such as silicon-based, fluorine-based, and polymer-based, phosphonates, phosphate derivatives, phosphorus compounds such as phosphazenes compounds, and other flame retardants and other ingredients. These can use known substances in the field of electronic materials. It should be noted that, in order to maintain the stability of the thermosetting resin composition, it is preferred that a silane coupling agent is not contained as an added component.

[0071] [Preparation method]

[0072] In the preparation of the thermosetting resin composition of the present invention, after weighing and mixing each component, it is pre-stirred with a stirrer. Then, each component is dispersed with a mixer, and it can be prepared by mixing. As the above-mentioned mixer, for example, a bead mill, a ball mill, a sand mill, a three-roll mill, a two-roll mill, etc. can be cited. The dispersion conditions such as the rotation ratio of each roll in the three-roll mill can be appropriately set according to the target viscosity.

[0073] [use]

[0074] The thermosetting resin composition of the present invention can be used to form a pattern layer as a permanent film of a printed wiring board such as a solder resist or a cover layer, an interlayer insulating layer, etc., and is particularly useful in the formation of an anti-corrosion agent (layer) such as a solder resist. In addition, since the thermosetting resin composition of the present invention can form a cured product with excellent film strength even if it is a thin film, it can also be applied to a printed wiring board requiring thin filmization, such as a printed wiring board used in a package substrate (a printed wiring board used in a semiconductor package) to form a pattern layer. In addition, since the cured product obtained by the thermosetting resin composition of the present invention has excellent flexibility, it can be applied to a flexible printed wiring board.

[0075] [cured material]

[0076] The cured product of the present invention is obtained by curing the thermosetting resin composition of the present invention. The cured product of the present invention can be applied to printed wiring boards. Since the cured product of the present invention has excellent flexibility, it can be particularly applied to flexible printed wiring boards.

[0077] [Printed wiring board]

[0078] The printed wiring board of the present invention comprises an insulating substrate and a resin layer composed of a cured product obtained from the above-mentioned thermosetting resin composition formed directly on the insulating substrate. Since the resin layer composed of the cured product obtained from the thermosetting resin composition of the present invention has excellent adhesion to the insulating substrate, the printed wiring board of the present invention has excellent heat resistance. In addition, the printed wiring board of the present invention is preferably white, and when white, the reflectivity of the resin layer is excellent, so it can be suitable for mounting LEDs.

[0079] As a method for manufacturing a printed wiring board of the present invention, for example, the thermosetting resin composition of the present invention is adjusted to a viscosity suitable for a coating method by using the above-mentioned organic solvent, and after coating it on an insulating substrate by a method such as screen printing, flow coating, roller coating, doctor blade coating, rod coating, etc., the organic solvent contained in the composition is volatilized and dried (pre-dried) for 15 to 90 minutes at a temperature of 60 to 100° C., thereby forming a surface-dried resin layer.

[0080] As the above-mentioned substrate, in addition to printed wiring boards or flexible printed wiring boards in which circuits are pre-formed with copper or the like, there are also substrates using materials such as copper-clad laminates for high-frequency circuits using paper phenol, paper epoxy, glass cloth epoxy, glass polyimide, glass cloth / non-woven epoxy, glass cloth / paper epoxy, synthetic fiber epoxy, fluororesin-polyethylene-polyphenylene ether, polyphenylene ether-cyanate ester, etc. Therefore, all grades (FR-4, etc.) of copper-clad laminates, as well as metal substrates, polyimide films, polyethylene terephthalate films, polyethylene naphthalate (PEN) films, glass substrates, ceramic substrates, chip boards, etc. can be cited.

[0081] The volatilization drying after coating the thermosetting resin composition of the present invention on the substrate can be carried out using a hot air circulation drying furnace, an IR furnace, a hot plate, a convection oven, etc. (using a device with a heat source of air heating method using steam, a method of making hot air convection contact in the dryer, and a method of spraying from a nozzle to the support). As an apparatus, as a hot air circulation drying furnace, DF610 manufactured by Yamato Scientific Co., Ltd. can be cited.

[0082] Example

[0083] Hereinafter, the present invention will be described in detail using examples, but the present invention is not limited to the following examples. It should be noted that "parts" and "%" in the following description are all based on mass unless otherwise specified.

[0084] (Synthesis of Hydroxyl-Containing Fluororesin 1)

[0085] Fluororesin 1 (copolymer of tetrafluoroethylene and vinyl acetate (molar ratio of tetrafluoroethylene and vinyl acetate = 1 / 1)) was prepared by a known method to obtain fluororesin 1 having a hydroxyl group and a hydroxyl value of 60 mg / g (KOH).

[0086] (Synthesis of Hydroxyl-Containing Fluororesin 2)

[0087] Fluororesin 2 (copolymer of chlorotrifluoroethylene and vinyl acetate (molar ratio of chlorotrifluoroethylene and vinyl acetate = 1 / 1) was prepared by a known method to obtain fluororesin 2 having a hydroxyl group and a hydroxyl value of 66 mg / g (KOH).

[0088] (Examples 1 to 23, Comparative Examples 1 to 8)

[0089] (Preparation of Thermosetting Resin Composition)

[0090] In each composition, each component was blended according to the blending shown in Tables 1 to 3 below, stirred with a stirrer, and then kneaded with a three-roll mill to prepare a thermosetting resin composition.

[0091] [Table 1]

[0092]

[0093] [Table 2]

[0094]

[0095] [Table 3]

[0096]

[0097] The blending amounts in Table 1 are expressed in parts by mass. Details of the components in Table 1 are as follows.

[0098] *1: The amount of the hydroxyl-containing fluororesin 1 synthesized above is a value based on solid content.

[0099] *2: Isocyanate compound 1 (trimer of isophorone diisocyanate, manufactured by Evonik Corporation, trade name: VESTANAT T1890).

[0100] *3: Isocyanate compound 2 (methyl ethyl ketoxime-based blocked diisocyanate, manufactured by Asahi Kasei Corporation, trade name: E402-B80B).

[0101] *4: Isocyanate compound 3 (ethanol-based blocked diisocyanate (silicate-based), manufactured by Shin-Etsu Chemical Co., Ltd., trade name: X-12-1159L).

[0102] *5: Isocyanate compound 4 (chain alkyl-based blocked diisocyanate, manufactured by Asahi Kasei Corporation, trade name SBB-70P).

[0103] *6: Bisphenol A type epoxy resin (manufactured by Mitsubishi Chemical Corporation, trade name: jER-825).

[0104] *7: Acrylic resin (manufactured by Sigma-Aldrich Corporation, trade name: poly(2-hydroxymethacrylate)).

[0105] *8: Rutile titanium oxide (average particle size 0.25 μm, manufactured by Ishihara Sangyo Co., Ltd., trade name: TIPAQUE CR-93).

[0106] *9: Silica (average particle size 0.1 μm, manufactured by Tosoh Silica Co., Ltd., trade name: Nipsil E743).

[0107] *10: The amount of the hydroxyl-containing fluororesin 2 synthesized above is a value based on solid content.

[0108] <Preparation of evaluation substrate>

[0109] (Examples 1 to 23, Comparative Examples 1 to 5, 8)

[0110] The thermosetting resin composition obtained in the examples and comparative examples was screen-printed on the entire surface of the copper foil so that the film thickness after drying was 25 μm. Thereafter, it was cured in a hot air circulation drying oven at 150° C. for 30 minutes to form a resin layer. The obtained evaluation substrate was evaluated as follows.

[0111] (Comparative Example 6)

[0112] The thermosetting resin composition obtained in Comparative Example 1 was applied to the entire surface of the copper foil by screen printing in a manner that the film thickness after drying was 13 μm, thereby forming a lower layer. Next, the thermosetting resin composition obtained in Example 2 was applied to the entire surface of the copper foil by screen printing in a manner that the film thickness after drying was 12 μm, thereby forming an upper layer, and cured in a hot air circulation drying oven at 150° C. for 30 minutes, thereby forming a resin layer. The obtained evaluation substrate was evaluated as follows.

[0113] (Comparative Example 7)

[0114] The thermosetting resin composition obtained in Example 2 was applied to the entire surface of the copper foil by screen printing in a manner that the film thickness after drying was 13 μm, thereby forming a lower layer. Next, the thermosetting resin composition obtained in Comparative Example 1 was applied to the entire surface of the copper foil by screen printing in a manner that the film thickness after drying was 12 μm, thereby forming an upper layer, and cured in a hot air circulation drying oven at 150° C. for 30 minutes, thereby forming a resin layer. The obtained evaluation substrate was evaluated as follows.

[0115] (Softness evaluation)

[0116] The storage modulus of the resin layer (cured product) formed on each evaluation substrate obtained above was measured using a dynamic viscoelasticity measuring device (DMA, manufactured by TA Instruments Japan Co., Ltd., model: RSA-G2). Based on the value of the storage modulus of the resin layer, the flexibility of the resin layer was evaluated according to the following criteria, and the evaluation results are shown in Tables 4 to 6.

[0117] [Evaluation criteria]

[0118] ○: The storage modulus is 0.02 GPa or more and 20 GPa or less.

[0119] ×: Storage modulus is less than 0.02 GPa or exceeds 20 GPa.

[0120] (Reflective evaluation)

[0121] The reflectivity of the resin layer formed on each evaluation substrate obtained above was measured using a spectrophotometer (manufactured by Konica Minolta, Inc., model: CM-2600d). Evaluation was performed based on the following criteria. The evaluation results are shown in Tables 4 to 6.

[0122] [Evaluation criteria]

[0123] ◎: The reflectivity is 89% or more.

[0124] ○: The reflectance is 86% or more and less than 89%.

[0125] ×: The reflectance is less than 86%.

[0126] In addition, reflectivity was also evaluated after the heat resistance evaluation described below according to the same evaluation criteria as above.

[0127] (Heat resistance evaluation)

[0128] A rosin-based flux was applied to each evaluation substrate obtained above, and immersed in a solder bath preset at 260° C. for 10 seconds. The flux was then cleaned with a modified alcohol. The blistering / peeling of the resin layer was visually evaluated according to the following criteria, and the evaluation results are shown in Tables 4 to 6.

[0129] [Evaluation criteria]

[0130] ○: The resin layer has no bubbling and peeling.

[0131] ×: The resin layer was obviously bubbling and peeling off.

[0132] (Warp Evaluation)

[0133] The thermosetting resin composition obtained in the examples and comparative examples was coated on a copper foil of 18 μm to form a coating film with a film thickness of 20 μm after drying. Thereafter, the obtained coating film was cut into 5 cm × 5 cm pieces, cured by heating at 150°C for 30 minutes, returned to room temperature and left to stand for 1 hour, and then the total height of the four corners from the table was measured. The warping of the resin layer was evaluated according to the following criteria, and the evaluation results are shown in Tables 4 to 6.

[0134] [Evaluation criteria]

[0135] ◎: Total height is less than ±20mm.

[0136] ○: The total height is more than ±20 mm and less than ±50 mm.

[0137] ×: The total height is ±50 mm or more.

[0138] [Table 4]

[0139]

[0140] [Table 5]

[0141]

[0142] [Table 6]

[0143]

[0144] The above experimental results show that the thermosetting resin composition of the present invention can form a resin layer having an excellent balance among flexibility, reflectivity, heat resistance and warpage.

[0145] On the other hand, in Comparative Examples 1 and 2, since no fluororesin is used in the thermosetting resin composition, it is difficult for the resin layer to have flexibility, reflectivity, heat resistance, and warpage at the same time.

[0146] In Comparative Example 3, although a fluororesin was used in the thermosetting resin composition, the mass ratio of titanium oxide to the fluororesin (titanium oxide / fluororesin) was too high, so the storage modulus (flexibility) was poor and warping could not be suppressed.

[0147] In Comparative Example 4, although a fluororesin was used in the thermosetting resin composition, the mass ratio of the fluororesin to the isocyanate compound (fluororesin / isocyanate compound) was too low, so it was difficult to achieve both reflectivity and heat resistance.

[0148] In Comparative Example 5, although a fluororesin was used in the thermosetting resin composition, the mass ratio of the fluororesin to the isocyanate compound (fluororesin / isocyanate compound) was too high, so the storage modulus (flexibility) was poor and warpage could not be suppressed.

[0149] In Comparative Examples 6 and 7, even if the resin layer is made into a two-layer structure of non-fluororesin layer / fluororesin layer, it is difficult to achieve both reflectivity and heat resistance as in the examples (fluororesin layer alone).

[0150] In Comparative Example 8, since the value of the mass ratio of titanium oxide to fluororesin (titanium oxide / fluororesin) was too low, the reflectivity was poor.

[0151] In Examples 18 to 21, it is found that the physical property values ​​are well balanced even though the chlorotrifluoroethylene copolymer is used instead of the tetrafluoroethylene copolymer. However, the reflectance is slightly inferior to that in the case of using tetrafluoroethylene.

[0152] In Examples 22 and 23, the influence of the silica content in the contained components was confirmed, but there was no significant effect.

[0153] (Elemental analysis results using the combustion method)

[0154] The thermosetting resin composition obtained in Examples 1, 5, 16 and Comparative Examples 1 and 8 was applied to a 50 μm release-treated PET to form a coating film with a film thickness of 20 μm after drying. Thereafter, after heating and curing at 150°C for 30 minutes and returning to room temperature and standing for 1 hour, the release PET was peeled off to obtain a self-supporting film. A test piece of about 10 mg was cut out from the film, and elemental analysis of nitrogen atomic weight and ash content was performed by combustion method (manufactured by Yanaco Co., Ltd., elemental analysis device MT-6). The measurement results are shown in Table 7.

[0155] In addition, the fluorine atomic weight was measured as follows. 5 mg of the test piece prepared in the same manner as above was taken as a measurement sample. Using the sample combustion device AQF-2100H manufactured by Nitto Seiko Analytical Science Co., Ltd., each measurement sample was subjected to combustion treatment by the quartz tube combustion method under the following conditions. The measurement results are shown in Table 7.

[0156] 1. Combustion conditions

[0157] (1) Heating conditions (heating section)

[0158] Room temperature → 1000℃, maintain for 3 minutes.

[0159] (2) Combustion conditions (combustion section)

[0160] Injection port (inlet): 900°C, discharge port (outlet): 1000°C.

[0161] (3) Burning time: 5 minutes (total).

[0162] 2. Gas conditions (all indicated by the flow meter on the device)

[0163] (1) Oxygen: 400 ml / min.

[0164] (2) Argon: 200 ml / min.

[0165] (3) Humidified argon: 100 ml / min.

[0166] (4)Total flow rate: 700 ml / min.

[0167] 3. The absorption liquid is 20 ml of 0.009% hydrogen peroxide water (after combustion treatment, the volume is fixed to 25 ml).

[0168] The fluorine concentration of the fixed volume absorbing solution obtained above was determined by ion chromatography under the following conditions.

[0169] Ion chromatograph: ICS-1100 (manufactured by Thermo Fisher Scientific).

[0170] Eluent: 2.7 mM Na2CO3 / 0.3 mM NaHCO3.

[0171] Column: IonPac AS12A (manufactured by Thermo Fisher Scientific Inc.).

[0172] Flow rate: 1.5ml / min.

[0173] Suppressor:AERS500.

[0174] Injection volume: 25μl.

[0175] [Table 7]

[0176] Example 1 Example 5 Example 16 Comparative Example 1 Comparative Example 8 Nitrogen atomic weight (mass %) 1.7 0.6 0.4 0.8 1.1 Ash content (mass %) 61 69.6 75.7 68 44 Fluorine atomic weight (mass %) 13.3 11.5 7.6 0 14.8

Claims

1. A thermosetting resin composition, characterized in that The thermosetting resin composition comprises: Hydroxyl-containing fluororesins; an isocyanate compound having two or more isocyanate groups; and Rutile titanium oxide, The amount of the rutile titanium oxide blended is 50% by mass or more, calculated as a solid content per part of the thermosetting resin composition. The mass ratio of the hydroxyl-containing fluororesin to the isocyanate compound is 1 or more and 20 or less, The mass ratio of the rutile titanium oxide to the hydroxyl-containing fluororesin is 1.4 or more and 4 or less.

2. The thermosetting resin composition according to claim 1, wherein The elemental analysis of the cured product obtained by curing the thermosetting resin composition by a combustion method revealed that, when the whole was defined as 100 mass %, the ash content was 45 mass % or more, the fluorine atoms were 3 mass % or more, and the nitrogen atoms were 0.1 mass % or more.

3. The thermosetting resin composition according to claim 1, wherein The mass ratio of the hydroxyl-containing fluororesin to the isocyanate compound is 2 to 10, and the mass ratio of the rutile titanium oxide to the hydroxyl-containing fluororesin is 1.8 to 3.

5.

4. The thermosetting resin composition according to claim 2, wherein The mass ratio of the hydroxyl-containing fluororesin to the isocyanate compound is 2 to 10, and the mass ratio of the rutile titanium oxide to the hydroxyl-containing fluororesin is 1.8 to 3.

5.

5. The thermosetting resin composition according to any one of claims 1 to 4, wherein The hydroxyl-containing fluororesin is a hydrolyzate of a copolymer of a fluorine-containing vinyl monomer and a vinyl ester monomer or a copolymer of a fluorine-containing vinyl monomer and a hydroxyl-containing vinyl monomer.

6. The thermosetting resin composition according to claim 5, wherein The fluorine-containing vinyl monomer is tetrafluoroethylene.

7. The thermosetting resin composition according to any one of claims 1 to 4 and 6, wherein The isocyanate compound is a blocked isocyanate.

8. The thermosetting resin composition according to claim 5, wherein The isocyanate compound is a blocked isocyanate.

9. The thermosetting resin composition according to any one of claims 1 to 4, 6 and 8, wherein The isocyanate compound contains a group containing an alkyl group, or a group containing an ether group and / or a silicate group.

10. The thermosetting resin composition according to claim 5, wherein The isocyanate compound contains a group containing an alkyl group, or a group containing an ether group and / or a silicate group.

11. The thermosetting resin composition according to claim 7, wherein The isocyanate compound contains a group containing an alkyl group, or a group containing an ether group and / or a silicate group.

12. The thermosetting resin composition according to any one of claims 1 to 4, 6, 8, 10 to 11, wherein A cured product obtained by curing the thermosetting resin composition has a storage modulus of 0.02 GPa or more and 20 GPa or less at 20°C.

13. The thermosetting resin composition according to claim 5, wherein A cured product obtained by curing the thermosetting resin composition has a storage modulus of 0.02 GPa or more and 20 GPa or less at 20°C.

14. The thermosetting resin composition according to claim 7, wherein A cured product obtained by curing the thermosetting resin composition has a storage modulus of 0.02 GPa or more and 20 GPa or less at 20°C.

15. The thermosetting resin composition according to claim 9, wherein A cured product obtained by curing the thermosetting resin composition has a storage modulus of 0.02 GPa or more and 20 GPa or less at 20°C.

16. The thermosetting resin composition according to any one of claims 1 to 4, 6, 8, 10 to 11, and 13 to 15, wherein The thermosetting resin composition is used for a resin layer directly formed on an insulating substrate.

17. The thermosetting resin composition according to claim 5, wherein The thermosetting resin composition is used for a resin layer directly formed on an insulating substrate.

18. The thermosetting resin composition according to claim 7, wherein The thermosetting resin composition is used for a resin layer directly formed on an insulating substrate.

19. The thermosetting resin composition according to claim 9, wherein The thermosetting resin composition is used for a resin layer directly formed on an insulating substrate.

20. The thermosetting resin composition according to claim 12, wherein: The thermosetting resin composition is used for a resin layer directly formed on an insulating substrate.

21. A solidified product, characterized in that: The cured product is a cured product obtained by curing the thermosetting resin composition according to any one of claims 1 to 20.

22. A printed wiring board, characterized in that: The printed wiring board includes an insulating substrate and a resin layer composed of the cured product according to claim 21 formed directly on the insulating substrate.

23. The printed wiring board according to claim 22, wherein The printed wiring board is used for a surface-mounted light-emitting diode.